2014
DOI: 10.4236/ojopm.2014.41003
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites Based on Natural Biodegradable Materials: Effect of Post-Preparative γ-Irradiation on the Swelling Properties

Abstract: Nanocomposites were prepared by in situ intercalative polymerization of acrylamide/acrylic acid in presence of fuller's earth. Agro-and food industry wastes, sugarcane bagasse and chitin, respectively were used as reinforcing/ adsorbent materials. Effect of γ-radiation on adsorption characteristics of nanocomposites was evaluated by the comparison of swelling and erosion measurements of the exposed and unexposed samples. Low doses of γ-radiation improved the characteristics as adsorbents. Better results were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
(19 reference statements)
1
0
0
Order By: Relevance
“…Keeping these soil moisture absorption and retention capacities as the focal point, Vundavalli et al [91] synthesized a novel biodegradable poly(acrylamide-co-acrylic acid)/silver-coated superabsorbent hydrogel nanocomposite for agricultural use. Electron microscopy scanning showed that the nanoparticles had a mean diameter of 200 nm which was akin to those reported earlier by Liu et al [98] and Bajpai et al [99]. The water absorbency rate of silver-coated hydrogel nanoparticles is comparatively higher in distilled water and tap water as compared to 1% sodium chloride solution whereas the water-holding ratio was 7.5% and 3.5% higher in the soil with silver-coated hydrogel and soil with hydrogel, respectively, when compared to original soil [91].…”
Section: Prospects Of Nano-based Hydrogel In Agriculturalsupporting
confidence: 84%
“…Keeping these soil moisture absorption and retention capacities as the focal point, Vundavalli et al [91] synthesized a novel biodegradable poly(acrylamide-co-acrylic acid)/silver-coated superabsorbent hydrogel nanocomposite for agricultural use. Electron microscopy scanning showed that the nanoparticles had a mean diameter of 200 nm which was akin to those reported earlier by Liu et al [98] and Bajpai et al [99]. The water absorbency rate of silver-coated hydrogel nanoparticles is comparatively higher in distilled water and tap water as compared to 1% sodium chloride solution whereas the water-holding ratio was 7.5% and 3.5% higher in the soil with silver-coated hydrogel and soil with hydrogel, respectively, when compared to original soil [91].…”
Section: Prospects Of Nano-based Hydrogel In Agriculturalsupporting
confidence: 84%